2004
DOI: 10.1074/jbc.m405624200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bioactivity of Neuropeptide F from the Human Parasites Schistosoma mansoni and Schistosoma japonicum

Abstract: The blood flukes Schistosoma mansoni and Schistosoma japonicum inflict immense suffering as agents of human schistosomiasis. Previous investigations have found the nervous systems of these worms contain abundant immunoreactivity to antisera targeting invertebrate neuropeptide Fs (NPFs) as well as structurally similar neuropeptides of the mammalian neuropeptide Y (NPY) family. Here, cDNAs encoding NPF in these worms were identified, and the mature neuropeptides from the two species differed by only a single ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
0
41
0
1
Order By: Relevance
“…A more compelling case for linking invertebrate NPF receptors to the inhibition of cAMP comes from schistosomes. Schistosome NPF inhibits the accumulation of cAMP in schistosome homogenates at a threshold of 10 x11 M (Humphries et al 2004). The inhibition is quite specific, with the most potent action reserved only for the endogenous schistosome peptide, but could also be reproduced less potently by mxNPF and porcine NPY.…”
Section: Physiology/biochemistry Of Flatworm Npfsmentioning
confidence: 98%
See 3 more Smart Citations
“…A more compelling case for linking invertebrate NPF receptors to the inhibition of cAMP comes from schistosomes. Schistosome NPF inhibits the accumulation of cAMP in schistosome homogenates at a threshold of 10 x11 M (Humphries et al 2004). The inhibition is quite specific, with the most potent action reserved only for the endogenous schistosome peptide, but could also be reproduced less potently by mxNPF and porcine NPY.…”
Section: Physiology/biochemistry Of Flatworm Npfsmentioning
confidence: 98%
“…Furthermore, there was chromatographic evidence that the parasite antigens were structurally similar to the 36 amino acid peptide common to NPY family members. Chromatographic analysis of peptide extracts from D. merlangi (Maule et al 1989 a), M. expansa (Maule et al 1991) and S. mansoni (Humphries et al 2004) found a single peak of PP immunoreactivity which co-eluted with other NPY family members from columns which separate on the basis of size and hydrophobicity. This type of evidence led to the hypothesis that there was an NPY-like neuropeptide present in flatworms even before the identification of a specific peptide from the phylum.…”
Section: Structure Of Flatworm Npfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the initial description (Maule et al, 1991), additional isoforms of NPF have been identified from members of many taxa, including the Rotifera, Platyhelminthes, Mollusca, Annelida and Arthropoda (e.g. Rajapara et al, 1992;Brown et al, 1999;Dougan et al, 2002;Stanek et al, 2002;Humphries et al, 2004;Roller et al, 2008;Nuss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%